Effect of Stiffness on Reflection and Transmission of Waves at an Interface between Heat Conducting Elastic Solid and Micropolar Fluid Media. (29th October 2014) - Kumar, Rajneesh; Rajvanshi, S. C.; Kaur, Mandeep
Abstract : The present investigation is concerned with the propagation of waves at an imperfect boundary of heat conducting elastic solid and micropolar fluid media. The amplitude ratios of various reflected and transmitted waves are obtained in a closed form due to incidence of longitudinal wave (P-wave), thermal wave (T-wave), and transverse wave (SV-wave). The variation of various amplitude ratios with angle of incidence is obtained for normal force stiffness, transverse force stiffness, thermal contact conductance, and perfect bonding. Numerical results are shown graphically to depict the effect of stiffness and thermal relaxation times on resulting quantities. Some particular cases are also deduced in the present investigation.